2023
DOI: 10.3390/ijerph20031943
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Transmission of Different SARS-CoV-2 Strains and Air Quality: A Case Study in China

Abstract: Coronavirus Disease 2019 (COVID-19) has been a global public health concern for almost three years, and the transmission characteristics vary among different virus variants. Previous studies have investigated the relationship between air pollutants and COVID-19 infection caused by the original strain of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, it is unclear whether individuals might be more susceptible to COVID-19 due to exposure to air pollutants, with the SARS-CoV-2 mutating fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…China, a study found a positive correlation between air pollutants (PM2.5, PM10, and NO2) and confirmed cases of COVID-19 caused by different SARS-CoV-2 strains. It suggested that the mutant variants appear to be more closely associated with air pollutants than the original strain [30]. Bangkok, Thailand a study found that people working near the streets, highways, and industrial zones tended to have more health symptoms related to low air quality, and informal sector workers faced more health risks than formal sector workers [31].…”
Section: Case Studies On Air Quality and Healthmentioning
confidence: 99%
“…China, a study found a positive correlation between air pollutants (PM2.5, PM10, and NO2) and confirmed cases of COVID-19 caused by different SARS-CoV-2 strains. It suggested that the mutant variants appear to be more closely associated with air pollutants than the original strain [30]. Bangkok, Thailand a study found that people working near the streets, highways, and industrial zones tended to have more health symptoms related to low air quality, and informal sector workers faced more health risks than formal sector workers [31].…”
Section: Case Studies On Air Quality and Healthmentioning
confidence: 99%
“…Additionally, the results demonstrated strong evidence that high levels of PM 2.5 exacerbated COVID-19 symptoms. The relationship between the transmission of different SARS-CoV-2 strains and several air quality criteria, including PM 2.5 in China, was recently explored [25] which revealed a positive correlation between PM 2.5 and confirmed cases of COVID-19 caused by different SARS-CoV-2 strains.…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of studies proposing the role of indoor airborne air transmission in the virus diffusion mechanism have been published ( Buonanno et al, 2022 ; Morawska et al, 2021 ; Peng et al, 2022 ). However, despite that several works were devoted to investigating the role of air pollutants, specifically, PM as an outdoor virus carrier ( Maleki et al, 2021 ), only a few studies are currently available about a possible air pollution-to-human role of PM in the spread dynamics of the SARS-CoV-2 Omicron variant (B.1.1.529), which is very contagious ( Ma and Ji, 2023 ).…”
Section: Introductionmentioning
confidence: 99%